PENGARUH KUALITAS PELAYANAN, SUASANA CAFÉ, DAN E-WOM TERHADAP LOYALITAS PELANGGAN DI MEDAN TANDA TANGAN PILASTRO - Ivy Joana; Yenni Martok (Jurnal Mahkota Bisnis (Makbis), 2023)
F&B industry, especially café is growing rapidly all around the world, including Medan Indonesia. It has been a trend lately to open a café, as people are seeking places to dine, socialize, relax, etc. As the competition in this industry is increasing day by day, companies need to maintain their business to be able to retain loyal customers for the business by improving the factors that influence their business. One of the cafés that is striving in this industry is Pilastro Signature Medan. The purpose of this research is to reveal whether the factors of Service Quality, Café Atmosphere, and E-WOM has an influence toward Customer Loyalty at Pilastro Signature Medan or not. This research is done by using the quantitative method and a descriptive research design. Sampling is done by using a non-probability sampling with the method of snowball sampling, which involves 96 respondents, and data are analysed using a multiple linear regression method. The result of this research reveals that Service Quality has a significant influence on Customer Loyalty, Café Atmosphere has a significant influence toward Customer Loyalty, E-WOM has a significant influence toward Customer Loyalty, and Service Quality, Café Atmosphere, and E-WOM simultaneously influence Customer Loyalty.